HUBUNGAN TINGKAT PENDIDIKAN, USIA, DAN PENGALAMAN KEJA TERHADAP PENDAPATAN PEKERJA WANITA PADA INDUSTRI KERAJINAN DOMPET IDA COLLECTION DI DESA PULO KECAMATAN TEMPEH KABUPATEN LUMAJANG - Nur Fitria Rochmawati; Wahyu Hidayat Riyanto; Ida Nuraini (Program Studi Ekonomi Pembangunan, 2018)
This study aims to look at the relationships that exist in the level of education, age, and work experience of the income of female handicraft female workers family in Pulo Village, Lumajang Regency. This research uses descriptive qualitative approach by using purposive sampling method in obtaining sample as much as 40 female handicraft woman in Pulo village and using Chi-Square data analysis method. From the analysis results obtained that the level of education and age have no significant effect on income. While in the variable work experience obtained significant results it is because the work experience can affect the level of output generated by workers.Keywords : Income Female Workers, Work Experience, Education Level, Age.